Developing Business Strategy for Local Television Network Into The Digital Broadcasting Competition in Indonesia: A JPM Case Study - Riska Dwi Firmiyanti; Arif Satria; Imam Teguh Saptono (School of Business, IPB University (SB-IPB), 2019)
The objective of this research is to identify the current Jawa Pos Multimedia (JPM) business model and to generate a design for its development to enhance competitiveness under a digital broadcast race in Indonesia. The research uses Business Model Canvas approach. Importance-Performance Analysis, EFE, IFE, SWOT and QSPM matrices are used as analytical tools in formulating the strategy. The research shows that the selected strategy is extensification and intensification of hyperlocal contents. Therefore on its business model, JPM needs to intensify personalization of hyperlocal content on its value proposition. Media asset management as well as research and development are added to the key activities. The hyperlocal contents become supplement into the key resources, whilst key partnerships must also be established with the media, OTT providers, social media, communities and video bloggers. The partnerships will also give impacts on growing number of channels with OTT and social media. Customer segments are expanded through Internet users and TV stations. Apart from social media line, there needs to be particular means of engagement to cultivate customer relations. Social media monetization, OTT ads and content rights are additional revenue potential tendered by the development of JPM business model.Keywords: BMC, business strategy, digital, broadcasting, local TV network